Orthogonal protection of saccharide polyols through solvent-free one-pot sequences based on regioselective silylations - Traboni, Serena; Bedini, Emiliano; Iadonisi, Alfonso (Beilstein Journal of Organic Chemistry, 2016)
tert-Butyldimethylsilyl (TBDMS) and tert-butyldiphenylsilyl (TBDPS) are alcohol protecting groups widely employed in organic synthesis in view of their compatibility with a wide range of conditions. Their regioselective installation on polyols generally requires lengthy reactions and the use of high boiling solvents. In the first part of this paper we demonstrate that regioselective silylation of sugar polyols can be conducted in short times with the requisite silyl chloride and a very limited excess of pyridine (2–3 equivalents). Under these conditions, that can be regarded as solvent-free conditions in view of the insolubility of the polyol substrates, the reactions are faster than in most examples reported in the literature, and can even be further accelerated with a catalytic amount of tetrabutylammonium bromide (TBAB). The strategy proved also useful for either the selective TBDMS protection of secondary alcohols or the fast per-O-trimethylsilylation of saccharide polyols. In the second part of the paper the scope of the silylation approach was significantly extended with the development of unprecedented “one-pot” and “solvent-free” sequences allowing the regioselective silylation/alkylation (or the reverse sequence) of saccharide polyols in short times. The developed methodologies represent a very useful and experimentally simple tool for the straightforward access to saccharide building-blocks useful in organic synthesis.
Keywords: carbohydrates; one-pot synthesis; regioselective protection; silyl protecting group; solvent-free reaction